2016
DOI: 10.1039/c6cp01650b
|View full text |Cite
|
Sign up to set email alerts
|

The critical size of hydrogen-bonded alcohol clusters as effective Brønsted bases in solutions

Abstract: The alkyl oxonium ion, which is a protonated alcohol, has long been proposed as a key reaction intermediate in alcohol dehydration. Nonetheless, the dynamics and structure of this simple but important intermediate species have not been adequately examined due to the transient nature of the oxonium ion. Here, we devised a model system for the key step in the alcohol dehydration reaction, in which a photoacid transfers a proton to alcohols of different basicity in the acetonitrile solvent. Using time-resolved sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…In neat ACN, AH + * was found to decay mainly in 9.1 ns (93%), which is ascribed to the lifetime of AH + * in the absence of ESPT. The minor component (7%) of the fluorescence decay is attributed to the complex of AH + with residual water as reported 4b …”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…In neat ACN, AH + * was found to decay mainly in 9.1 ns (93%), which is ascribed to the lifetime of AH + * in the absence of ESPT. The minor component (7%) of the fluorescence decay is attributed to the complex of AH + with residual water as reported 4b …”
Section: Resultssupporting
confidence: 68%
“…For proton transfer to occur, the formation of an encounter acid–base complex by hydrogen (H)‐bonding is prerequisite. Through a series of studies, this group has revealed the cooperative nature of H‐bonding of alcohol as a base in the acid–base reactions with a strong photoacid 4 . The cooperative nature of H‐bonds in alcohol clusters originates from the increase of negative charge density on the proton‐accepting oxygen atom of the alcohol molecule, which donates a H‐bond to another alcohol molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…63 The concerted action of a pair of water or alcohol molecules in proton transfer reactions has also been demonstrated. [64][65][66][67] Electron transfer from water or alcohols to other excited chromophores has also been established. Femtosecond experiments in bulk solvents showed that excited oxazine 750 is reduced by different aliphatic alcohols.…”
Section: Involvement Of An Electron Transfer Process In the Quenchingmentioning
confidence: 99%
“…A hydrogen bond is an important interaction dominating the structural conformation of a DNA double chain and the reactivity of clusters . The strength of the hydrogen bond sometimes determines the reaction mechanism of the clusters …”
Section: Introductionmentioning
confidence: 99%